COMMUNITY MOVEMENT IN WASTE MANAGEMENT (Case in Cikapundung River Basin in Bandung City) - Bintarsih Sekarningrum; Desi Yunita (Prodi Sosiologi FISIP Universitas Teuku Umar, 2015)
There is a connection between the behaviour of throwing waste into the river with the community perspective about river. The behaviour of people throwing waste into the river assosiated with the lack of availability of facilities dispose of waste in the area and looked at the river as an object or place that is easiest to throw garbage into the river. Related to these problems, this research describes the community who doing the social movement in waste management a long the river, as well as analyzing patterns of community organizing in waste management.The approach used is a qualitative method of data collection techniques consisted of observation, interviews and focus group discussions. Research shows that the government has made efforts through the program